A Catalog of Active Galactic Nuclei from the First 1.5 Gyr of the Universe - Perger, Krisztina; Frey, Sándor; Gabányi, Krisztina É.; Tóth, L. Viktor (Frontiers in Astronomy and Space Sciences, 2017)
Active galactic nuclei (AGN) are prominent astrophysical objects that can be observed throughout the whole Universe. To understand the underlying physical processes and the different appearance of AGN types, extensive samples are needed. Nowadays, various AGN catalogs are available at different wavebands. However, at the highest redshifts data are still relatively sparse. These data are required for examining AGN properties in the early Universe. This way we can compare the earliest AGN with those seen at lower redshifts, and can study their cosmological evolution. Additionally, because of their high luminosity, AGN may also be used as probes to test cosmological models. With the aim of constructing a complete sample of all known AGN at z ≥ 4, we are currently compiling a photometric catalog from literature sources. We cross-match catalogs particularly at optical and radio wavebands, to build up a sample for detailed high-resolution radio interferometric studies. The continuously updated list now contains nearly 2,600 objects with known spectroscopic redshifts, optical magnitudes, and auxiliary information about observations at other wavebands. About 170 of them are known radio sources for which we collect existing radio interferometric data from the literature.